2015
DOI: 10.1016/j.heliyon.2015.e00010
|View full text |Cite
|
Sign up to set email alerts
|

Comparative alteration in atherogenic indices and hypocholesteremic effect of palm oil and palm oil mill effluent in normal albino rats

Abstract: The comparative hypocholesteremic effect of feeding palm oil and palm oil mill effluent (POME) was investigated in male albino rats. Diets were prepared and designed to contain 50% of energy as carbohydrate, 35% as fat, and 15% as protein. Groups of six rats were each fed one of these diets, while a group was fed pelletized mouse chow which served as the control. Feeding on palm oil and POME led to a significant increase (p < 0.05) in serum total cholesterol, triglyceride, and vLDL. Feeding on POME led to sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…These two pools of data demonstrated a significant finding on the safe consumption of this oil, as well as a potential agent to reduce the concentration of LDL-C. It is important to note that out of the nine studies, only one study reported unfavorable effects of the PO on serum or plasma LDL-C concentration after 6 weeks of consumption, in which the amount of oil incorporated into the diet was the highest (35%) among other studies selected in this review (26). Despite the significant increment in serum LDL-C concentration, Ajiboye et al reported no changes in other lipid variables such as TC, TG and HDL-C compared to the control group.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…These two pools of data demonstrated a significant finding on the safe consumption of this oil, as well as a potential agent to reduce the concentration of LDL-C. It is important to note that out of the nine studies, only one study reported unfavorable effects of the PO on serum or plasma LDL-C concentration after 6 weeks of consumption, in which the amount of oil incorporated into the diet was the highest (35%) among other studies selected in this review (26). Despite the significant increment in serum LDL-C concentration, Ajiboye et al reported no changes in other lipid variables such as TC, TG and HDL-C compared to the control group.…”
Section: Discussionmentioning
confidence: 84%
“…Another two studies conducted showed that the animals were provided with 1 mL of palm olein per day (route of administration was not mentioned) (30) and 2.5 mL of PO per day given through the oral administration (25). The majority of the studies used serum [ (24)(25)(26)(27), (28,29,31)] for the lipid profile analysis. All studies measured four lipid variables (TC, TG, HDL-C, and LDL-C) in their lipid profile study.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…19 The HDL-cholesterol level was determined with the method of Ajiboye. 20 The level of triglycerides was estimated according to Deori method. 21 Mohun and Cook methods were used to determine the Alanine aminotransferase (ALT) level.…”
Section: Biochemical Parametersmentioning
confidence: 99%